Traditional Herbal Cosmetics Used By Ethnic Groups in South-East Rajasthan as a Skin Care: Exploring the traditional use of herbal cosmetics in South-East Rajasthan (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Natural beauty is blessing and cosmetics help in enhancing the beauty and personality aspects of human beings. Since ancient times women uses many herbs to increase their own beauty. Even today, people especially in rural areas depend upon plants for traditional cosmetics. Nature has offered the way to keep up that parity. A herb is a plant or plant extract, including leaves, bark, berries, roots, gums, seeds, stems and flowers which contain nourishing and healing elements. Herbal cosmetics have improved much popularity among the population. Herbal cosmetics products do not have adverse effects which are commonly seen in synthetic products.The research work is confined to herbal cosmetics with special reference of local communities of Hadoti region (Rajasthan). Through questionnaires, study was conducted in different villages of Hadoti region to collect information from localtribal people for having the detailed knowledge of herbal cosmetics and their conservation. Indigenous data on 37 herbal recipes for skin care were collected from respondent informants.